Allium Vegetables, Garlic Supplements, and Risk of Cancer: A Systematic Review and Meta-Analysis - Zhang, Qifan; Zhao, Qing; Shen, Yan; Zhao, Fuping; Zhu, Yan (Frontiers in Nutrition, 2022)
Purpose The role of allium vegetables or garlic supplements on reducing cancer risk was inconsistent between laboratory study findings and related epidemiologic studies. Methods Studies assessing the effect of allium vegetables and garlic supplement consumption on cancer risk were included in our meta-analysis. We used fixed- or random-effects models to pool effect measures to evaluate the highest and lowest consumption. A dose-response regression analysis was used to assess the association between allium vegetables, garlic supplements, and cancer risk. Results In a pooled analysis of 22 studies with 25 reports on allium vegetables, a high consumption of allium vegetables showed no significant association with cancer risk (relative risk [RR] = 0.97, 95% confidence interval [CI] 0.92–1.03) in a fixed-effects model. Similarly, garlic supplements were not found to be significantly associated with an increased risk of cancer (RR = 0.97, 95% CI 0.84–1.12) in a random-effects model involving a pooled analysis of 10 studies with 11 reports. Consumption of allium vegetables did not significantly correspond with cancer risk (P for nonlinearity = 0.958, P for linearity = 0.907). Conclusion In this meta-analysis, we found no evidence that higher consumption of allium vegetables or garlic supplements reduced the risk of cancer; however, this finding requires further validation. Systematic Review Registration https://www.crd.york.ac.uk/prospero/#recordDetails, identifier: CRD42021246947.